Sphenoid sinus mucoceles - Devarasetty, Amarnath; Natarajan, Kiran; Begum, Thangammal; R. S., Anand kumar; Kameswaran, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Mucoceles are cyst-like lesions lined with respiratory epithelium that most commonly produce bone destruction within the paranasal sinuses. The spread of mucoceles is variable; hence they may cause different symptoms. In a majority of patients, mucoceles involve the frontal sinuses and the ethmoidal labyrinth. Sphenoidal mucoceles are rare and have an incidence of 1%. Prompt management of sphenoidal mucoceles is recommended in order to avoid potentially devastating complications. Our objective was to analyze the various presenting symptoms & signs of sphenoid mucoceles in twelve patients and the outcomes of management. Methods: Twelve patients were diagnosed with sphenoidal mucocele over an 18 year period (January 1998 - December 2015). All patients underwent diagnostic nasal endoscopy, CT / MRI scans prior to management. Results: Twelve patients with sphenoid mucocele presented with variable signs & symptoms to a tertiary ENT care facility. All patients were successfully managed by endoscopic sinus surgery. Two out of three patients with diminished vision had complete recovery of vision after the procedure. One patient with complete loss of vision had no recovery after endoscopic sinus surgery. Conclusions: Imaging plays a vital role in diagnosis of sphenoid mucoceles. The close proximity of the optic nerve to the sphenoid sinus makes it very vulnerable to get involved. Early diagnosis and management of sphenoid mucoceles is crucial.